Children's eating behavior, feeding practices of parents and weight problems in early childhood: results from the population-based Generation R Study - Jansen Pauline W; Roza Sabine J; Jaddoe Vincent WV; Mackenbach Joreintje D; Raat Hein; Hofman Albert; Verhulst Frank C; Tiemeier Henning (BMC, 2012)
Abstract Background Weight problems that arise in the first years of life tend to persist. Behavioral research in this period can provide information on the modifiable etiology of unhealthy weight. The present study aimed to replicate findings from previous small-scale studies by examining whether different aspects of preschooler's eating behavior and parental feeding practices are associated with body mass index (BMI) and weight status -including underweight, overweight and obesity- in a population sample of preschool children. Methods Cross-sectional data on the Child Eating Behaviour Questionnaire, Child Feeding Questionnaire and objectively measured BMI was available for 4987 four-year-olds participating in a population-based cohort in the Netherlands. Results Thirteen percent of the preschoolers had underweight, 8% overweight, and 2% obesity. Higher levels of children's Food Responsiveness, Enjoyment of Food and parental Restriction were associated with a higher mean BMI independent of measured confounders. Emotional Undereating, Satiety Responsiveness and Fussiness of children as well as parents' Pressure to Eat were negatively related with children's BMI. Similar trends were found with BMI categorized into underweight, normal weight, overweight and obesity. Part of the association between children's eating behaviors and BMI was accounted for by parental feeding practices (changes in effect estimates: 20-43%), while children's eating behaviors in turn explained part of the relation between parental feeding and child BMI (changes in effect estimates: 33-47%). Conclusions This study provides important information by showing how young children's eating behaviors and parental feeding patterns differ between children with normal weight, underweight and overweight. The high prevalence of under- and overweight among preschoolers suggest prevention interventions targeting unhealthy weights should start early in life. Although longitudinal studies are necessary to ascertain causal directions, efforts to prevent or treat unhealthy child weight might benefit from a focus on changing the behaviors of both children and their parents.